PENGUJIAN NESS-APP UNTUK DETEKSI SARANG BURUNG WALET TESTING OF NESS-APP FOR DETECTING SWIFTLET NESTS - Parhusip, Hanna Arini; Trihandaru, Suryasatriya; Indrajaya, Denny; Hartomo, Kristoko Dwi; Lewerissa, Karina Bianca; Mahastanti, Linda Ariany (Universitas Mataram, 2024)
This article discusses the development and testing of the Ness-App application, designed to detect and assess the quality of swallow nests effectively and efficiently. The main issue addressed is the difficulty in determining the quality of swallow nests through photos or videos in buying and selling transactions. The purpose of this research is to develop an Android application using object detection technology to assist PT. Waleta Asia Jaya in assessing the quality of swallow nests. The method used involves creating an object detection model using Convolutional Neural Network (CNN) and SSD MobileNet architecture. The results indicate that the Ness-App application can improve transaction efficiency and quality, providing a better understanding of swallow nest conditions for collectors and farmers. In conclusion, Ness-App supports digitalization and technological advancement in the swallow nest industry by providing an effective tool for quality assessment and accelerating the transaction process.